Method for improving surface gloss stability of acrylonitrile-butadiene-styrene copolymer composition

By mixing native and regenerated acrylonitrile-butadiene-styrene copolymers and undergoing thermal composite treatment, the gloss stability problem of ABS components at high temperatures is solved, and higher gloss and visual effects are achieved.

CN119213073APending Publication Date: 2024-12-27INEOS STYROLUTION GRP GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040943.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-18
Filing Date
2023-05-16
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art has failed to effectively improve the surface gloss stability of molded ABS components after long-term storage at high temperatures, and the existing improvement methods are complex and economically unfeasible.

Method used

By mixing native acrylonitrile-butadiene-styrene copolymer (v-ABS) with 10-99% by weight regenerated acrylonitrile-butadiene-styrene copolymer (r-ABS), and regenerated ABS is The thermal compounding treatment is performed before mixing to form an improved ABS composition.

Benefits of technology

The surface gloss stability of the ABS composition is significantly improved, especially after 1000 hours at 80°C, the glossiness of the mixture is higher than that of pure native ABS, and the optical properties and visual appearance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137022950000171
    Figure BDA0005137022950000171
Patent Text Reader

Abstract

The present invention relates to a method for providing an acrylonitrile-butadiene-styrene copolymer composition (ABS) with improved surface gloss stability, the process is by mixing a native acrylonitrile-butadiene-styrene copolymer composition (v-ABS) with 10-99% by weight of at least one regenerated acrylonitrile-butadiene-styrene copolymer composition (r-ABS) based on the ABS. Wherein the at least one regenerated acrylonitrile-butadiene-styrene copolymer composition (r-ABS) is subjected to at least one separate thermal compounding step prior to the mixing step. Also disclosed are a process for preparing the ABS composition and the use of the ABS composition for preparing a molding composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for providing an acrylonitrile-butadiene-styrene copolymer composition (ABS) having improved surface gloss stability by mixing a virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) with at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS). Background Art

[0002] Acrylonitrile-butadiene-styrene (ABS) copolymer compositions have been known for decades and are commonly used in consumer products. It is well known that high surface gloss ABS can be obtained using rubber particles with an average particle size equal to or less than the wavelength of visible light. While bulk polymerized ABS (particle size is typically 300nm-5μm) tends to show only low surface gloss, emulsion polymerized ABS (particle size is typically 100nm-400nm) shows higher surface gloss (see Practical Guide to Structures, Properties and Applications of Styrenic Polymers; N. Niessner, D. Wagner; Smithers, 2013).

[0003] In practical applications, it is important to maintain the gloss level of ABS, even when used at high temperatures for long periods of time. A proven method to improve surface gloss retention is to use antioxidants and / or auxiliary stabilizers, such as sulfur and / or nitrite components. Such solutions are complex and may not be economically viable.

[0004] KR 2010-0122303 discloses an ABS composition with good gloss properties, comprising 100 parts by weight of a thermoplastic ABS base resin and 0.01-0.5 parts by weight of a modified acrylic copolymer. The base resin comprises 25-40% by weight of an ABS copolymer and a conjugated diene rubber copolymer grafted with a vinyl aromatic compound and acrylonitrile; 10-45% by weight of a copolymer of acrylonitrile and a vinyl aromatic compound; and 25-50% by weight of a recycled thermosetting resin.

[0005] WO 2021 / 110751 (INEOS Styrolution) discloses a thermoplastic molding composition comprising a recycled polymer material A containing a recycled acrylonitrile-butadiene-styrene copolymer (r-ABS) as component A1, a graft copolymer A different from A, and at least one block copolymer C. The document relates to a method for preparing a thermoplastic molding composition, its use for preparing a molded article, and the prepared molded article.

[0006] WO 2021 / 074084 (INEOS Styrolution) discloses the need to add at least two different virgin materials to adjust the properties of recycled ABS (r-ABS) so that the obtained blend is within a predetermined range of mechanical, thermal and flow properties. The study found that the addition of at least two virgin materials selected from acrylonitrile-butadiene-styrene copolymer (ABS), styrene-acrylonitrile copolymer (SAN), styrene-butadiene block copolymer (SBC) and lubricant is conducive to obtaining high-quality and stable quality recycled ABS products, and can well balance the required properties.

[0007] The prior art fails to disclose a method for improving the surface gloss stability of molded ABS parts after long-term storage at high temperatures. It has now surprisingly been found that the surface gloss stability of ABS compositions can be significantly improved by mixing recycled ABS with virgin ABS compositions. Although the initial gloss of the virgin ABS composition is higher than that of the recycled ABS, after 1000 hours at 80°C, the gloss of the mixture of recycled ABS and virgin ABS is higher than that of pure virgin ABS. Summary of the invention

[0008] The present invention relates to a method for improving the gloss stability of an acrylonitrile-butadiene-styrene copolymer composition (ABS), wherein the method comprises mixing a virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) with 10-99% by weight of at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) based on the acrylonitrile-butadiene-styrene copolymer composition, wherein the at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) is subjected to at least one separate thermal compounding step before the mixing step, wherein the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) is a virgin material comprising:

[0009] A: 20-60% by weight of at least one graft copolymer A, comprising (or consisting of):

[0010] A1: Based on the solid content of the graft copolymer A, 40-85% by weight of a graft substrate A1, comprising:

[0011] A11: 0-21% by weight, based on the graft base A1, of at least one vinyl aromatic monomer, in particular styrene, and

[0012] A12: 79-100% by weight butadiene, based on the grafting matrix A1,

[0013] wherein the sum of A11 and A12 is 100% by weight of the grafting matrix A1; and

[0014] A2: 15-60% by weight, based on the solid content of the graft copolymer A, of at least one graft shell A2, comprising:

[0015] A21: 70 to 90% by weight, based on the graft shell A2, of styrene and / or α-methylstyrene, in particular styrene, and

[0016] A22: 10-30% by weight of acrylonitrile, based on graft shell A2,

[0017] wherein the sum of A21 and A22 is 100% by weight of the graft shell A2; and

[0018] wherein the sum of the graft matrix A1 and the graft shell A2 is 100% by weight of the graft copolymer A;

[0019] B: 40-80% by weight of at least one thermoplastic copolymer B, comprising:

[0020] B1: 20-31% by weight of acrylonitrile, based on copolymer B, and

[0021] B2: 69-80% by weight of styrene or α-methylstyrene or a mixture of styrene and α-methylstyrene, based on copolymer B;

[0022] wherein the sum of B1 and B2 is 100% by weight of the thermoplastic copolymer B; and

[0023] C: 0-5% by weight of at least one additive C;

[0024] Wherein, the sum of A, B and C is equal to 100 weight percent of the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS).

[0025] The method of the present invention provides, inter alia, a post-consumer recycled product based on ABS copolymers with improved gloss stability and a method for preparing the same.

[0026] For the purposes of the present invention, the term "virgin material" or "virgin acrylonitrile-butadiene-styrene copolymer (v-ABS)" refers to a material made from geological resources (e.g., oil-based geological resources) rather than from existing and especially post-consumer materials. For the purposes of the present invention, virgin polymeric material refers to a polymer made from geological resources (e.g., petroleum) rather than from existing and especially post-consumer plastic materials.

[0027] For the purposes of the present invention, the term "recycled material" or "recycled acrylonitrile-butadiene-styrene copolymer (r-ABS)" refers to a polymer of the acrylonitrile-butadiene-styrene copolymer type prepared from waste plastic materials, especially recycled durable goods, usually during recycling processing and separation. The recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) has been through at least one separate thermal compounding step, for example, an extrusion process or an injection molding process, before the mixing step.

[0028] For the purposes of the present invention, "durable goods" or "recycled durable goods" refer to goods such as household appliances, machinery, sports equipment, consumer electronics and automobiles that are not rapidly consumed or destroyed during use but are expected to continue to be used and produce long-term utility, especially for three years or more. And, "post-consumer products" or "post-consumer durable goods" refer to products or goods after their intended use, especially after their use for three years or more, such materials are collected and recycled in the form of waste plastic materials, for example.

[0029] Preferably, the method comprises a process step of mixing the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) with 10-99% by weight, more preferably 30-89% by weight, for example 40-80% by weight or 45-75% by weight, typically 50-70% by weight of a recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) based on the acrylonitrile-butadiene-styrene copolymer composition (ABS).

[0030] Surprisingly, the optical properties of an acrylonitrile-butadiene-styrene copolymer composition (ABS) obtained by mixing a virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) with 10-99% of at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) are superior to those of pure virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) and pure recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS), and the surface gloss, gloss stability and visual appearance after artificial weathering are improved.

[0031] According to the present invention, gloss stability is preferably determined by comparing the surface gloss of a molded article formed from an acrylonitrile-butadiene-styrene copolymer composition (ABS) before and after aging at 80°C for 1000 hours with the surface gloss of a molded article formed from a virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS).

[0032] The components of v-ABS and r-ABS will be described in further detail below.

[0033] Virgin acrylonitrile butadiene styrene (v-ABS)

[0034] According to the present invention, the method uses a virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS), which is a virgin material comprising:

[0035] A: 20-60% by weight of at least one graft copolymer A, comprising:

[0036] A1: Based on the solid content of the graft copolymer A, 40-85% by weight of the graft matrix A1, comprising:

[0037] A11: 0-21% by weight, based on the graft base A1, of at least one vinyl aromatic monomer, in particular styrene, and

[0038] A12: 79-100% by weight of butadiene, based on the grafting matrix A1;

[0039] wherein the sum of A11 and A12 is 100% by weight of the grafting matrix A1; and

[0040] A2: 15-60% by weight, based on the solid content of the graft copolymer A, of at least one graft shell A2, comprising:

[0041] A21: 70 to 90% by weight, based on the graft shell A2, of styrene and / or α-methylstyrene, in particular styrene, and

[0042] A22: 10-30% by weight of acrylonitrile, based on the graft shell A2,

[0043] wherein the sum of A21 and A22 is 100% by weight of the graft shell A2; and

[0044] wherein the sum of the graft matrix A1 and the graft shell A2 is 100% by weight of the graft copolymer A;

[0045] B: 40-80% by weight of at least one thermoplastic copolymer B, comprising:

[0046] B1: 20-31% by weight of acrylonitrile, based on copolymer B, and

[0047] B2: 69-80% by weight of styrene or α-methylstyrene or a mixture of styrene and α-methylstyrene, based on copolymer B;

[0048] The sum of B1 and B2 is 100% by weight of the thermoplastic copolymer B.

[0049] Such virgin acrylonitrile-butadiene-styrene copolymer compositions (v-ABS) are generally known in the art and are described, for example, in the literature.

[0050] Graft copolymer A generally comprises:

[0051] A1: 40-85% by weight of graft matrix A1, based on the solid content of graft copolymer A, can be obtained by polymerizing the following components:

[0052] A11: 0-21% by weight, based on the graft base A1, of at least one vinyl aromatic monomer, in particular styrene, and

[0053] A12: 79-100% by weight, based on the graft base A1, of at least one diene, in particular butadiene;

[0054] wherein the sum of A11 and A12 is 100% by weight; and

[0055] Aggregating the obtained grafted matrix A1 using an agglomerating agent C; and

[0056] A2: 15-60% by weight of graft shell, based on the solid content of graft copolymer A, obtained by reacting aggregated graft base A1 with the following mixture:

[0057] A21: 70 to 90% by weight, based on the graft shell A2, of styrene and / or α-methylstyrene, in particular styrene, and

[0058] A22: 10-30% by weight of acrylonitrile and / or methyl methacrylate, especially acrylonitrile, based on the graft shell A2;

[0059] The total weight of the graft base A1 and the graft shell A2 is 100% by weight of the graft copolymer A.

[0060] The graft base A1 usually uses a diene component A12 in an amount of 79-100% by weight, preferably 90-98% by weight, and a vinyl aromatic component A11 in an amount of 0-21% by weight, preferably 2-10% by weight.

[0061] The component A11 used may be α-methylstyrene and / or styrene, preferably only styrene. The diene component A12 used may be, for example, isoprene and / or butadiene, preferably butadiene.

[0062] The preferred graft base A1 consists of butadiene and styrene in the above-mentioned composition.

[0063] Preferably, the graft base A1 is prepared by emulsion polymerization and agglomerated by means of the agglomerating agent C. Means for preparing suitable graft bases A1 are known in the art and are described, for example, in DE 102005022632 or WO 2014 / 170406.

[0064] The dispersion of the aggregated graft base A1 obtained is relatively stable and can be easily stored and transported without visible solidification. The aggregated graft base A1 is used to prepare the graft copolymer A.

[0065] To prepare the graft copolymer A, the aggregated graft base A1 is grafted with at least one graft shell A2 which comprises monomers A21 and A22.

[0066] The graft copolymer A generally comprises 40-85% by weight of the graft base A1 and 15-60% by weight of the graft shell A2, based on the solids content of the graft copolymer A. The sum of A1 and A2 is 100% by weight.

[0067] The graft shell A2 can be obtained by reacting the following substances:

[0068] A21: 70-90% by weight, preferably 75-85% by weight, of styrene and / or α-methylstyrene, especially styrene, and

[0069] A22: 10-30% by weight, preferably 15-25% by weight of acrylonitrile, methacrylonitrile and / or methyl methacrylate, especially acrylonitrile, in the presence of the aggregated grafting matrix A1. The sum of A21 and A22 is 100% by weight.

[0070] Preferably, the graft shell A2 consists of an A2-1 copolymer of styrene and acrylonitrile and an A2-2 copolymer of α-methylstyrene and acrylonitrile. Particular preference is given to the A2-1 copolymer of styrene and acrylonitrile. Particularly preferred graft shells A2 are obtained by reacting 75-85% by weight of styrene and 15-25% by weight of acrylonitrile.

[0071] The graft shell A2 is preferably prepared by an emulsion polymerization process after agglomeration of the graft base A1.

[0072] Preferably, the virgin ABS (v-ABS) comprises a graft copolymer A having a particle size distribution D 50 It is 70nm-550nm, preferably 80nm-450nm, usually 100nm-400nm.

[0073] Weight median particle size D 50It refers to the diameter that precisely divides the particle into two equal parts. The weight median particle diameter D of the particles with a weight percentage of 50% 50 Large, 50% by weight of particles larger than the median particle size D 50 Small. Weight median particle size D 50 The value can be determined using an ultracentrifuge (for example as described in W. Scholtan, H. Lange: Kolloid Z. uZ Polymere 250, pp. 782-796 (1972)) or a disc centrifuge (for example the DC 24000 from CPS Instruments Inc.).

[0074] Details on the properties of the grafting reactions are known to the person skilled in the art and are disclosed, for example, in DE-A 2427960, EP-A 0062901 or WO 2014 / 170406 (see "Pfropfcopolymer B, Allgemeine Vorgehensweise", pages 34-35).

[0075] Graft copolymers A obtained from the following components are preferred:

[0076] A1: 40-85% by weight of graft matrix A1, based on the solid content of graft copolymer A, obtained by:

[0077] (a) Polymerization:

[0078] A11: 0-21% by weight of styrene based on the graft base A1, and

[0079] A12: 79-100% by weight butadiene, based on the grafting matrix A1,

[0080] wherein the sum of A11 and A12 is 100% by weight; and

[0081] (b) agglomerating the obtained graft base A1 by adding the following components:

[0082] C: Based on 100 parts by weight of graft base A1, in each case based on the solids content, 0.01 to 5 parts by weight of a coacervate copolymer C of the following components:

[0083] C1: 80-99.9% by weight of ethyl acrylate, and

[0084] C2: 0.1-20% by weight of methacrylamide,

[0085] wherein the sum of C1 and C2 is 100% by weight; and

[0086] A2: 15-60% by weight of graft shell, based on the solid content of graft copolymer A, obtained by reacting the aggregated graft base A1 with the following mixture:

[0087] A21: 70-90% by weight of styrene, based on graft shell A, and

[0088] A22: 10-30% by weight of acrylonitrile based on graft shell A;

[0089] The sum of the graft base A1 and the graft shell A2, based on the graft copolymer A, is 100% by weight.

[0090] The thermoplastic copolymer B is preferably prepared from the components acrylonitrile and styrene and / or α-methylstyrene by bulk polymerization or in the presence of one or more solvents. Copolymer B with a mass average molar mass Mw of 50,000-300,000 g / mol is preferred, wherein the mass molar mass can be determined, for example, by GPC with tetrahydrofuran as solvent and UV detection. The thermoplastic copolymer B forms the thermoplastic matrix of the native acrylonitrile-butadiene-styrene copolymer composition (v-ABS). The number average molar mass (Mn) of copolymer B is preferably 15,000-100,000 g / mol (determined by GPC with tetrahydrofuran as solvent and UV detection). The viscosity of copolymer B (determined in 0.5% by weight DMF solution at 25° C. according to DIN 53726) is, for example, 50-120 ml / g.

[0091] The thermoplastic copolymer B may especially comprise (or consist of):

[0092] (Ba) poly(styrene-acrylonitrile) prepared from 69 to 80% by weight of styrene and 20 to 31% by weight of acrylonitrile, in each case based on the total weight of (Ba), or

[0093] (Bb) poly(α-methylstyrene-acrylonitrile), prepared from 69 to 80% by weight of α-methylstyrene and 20 to 31% by weight of acrylonitrile, in each case based on the total weight of (Bb), or

[0094] (Bc) A mixture of the copolymer matrix (Ba) and the copolymer matrix (Bb).

[0095] Thermoplastic copolymers B can also be obtained by copolymerization of acrylonitrile, styrene and α-methylstyrene. In principle, however, polymer matrices containing other monomer building blocks can also be used.

[0096] Thermoplastic copolymers B can be prepared, for example, by bulk / solution polymerization, for example according to the process described in Kunststoff-Handbuch, Vieweg-Daumiller, Vol. 5, (Polystyrol), Carl-Hanser-Verlag, Munich 1969, pp. 122-123, lines 12 ff., in toluene or ethylbenzene.

[0097] As mentioned above, preferably copolymer component B is poly(styrene-acrylonitrile), poly(α-methylstyrene-acrylonitrile) or a mixture thereof. In a preferred embodiment, component B is isolated after preparation according to methods known to those skilled in the art and preferably processed into pellets.

[0098] Based on the total virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS), the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) may contain up to 5% by weight, preferably up to 3% by weight, of one or more other additives C. Preferably, based on the total virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS), the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) may contain 0.01-5% by weight, preferably 0.1-2.5% by weight of one or more additives C.

[0099] Additives C are generally selected from known additives for styrene polymers and copolymers and compositions thereof, commonly used for processing or finishing polymers.

[0100] Examples include, for example, dyes, pigments, colorants, antistatic agents, antioxidants, stabilizers for improving thermal stability, stabilizers for increasing light stability, stabilizers for enhancing hydrolysis resistance and chemical resistance, anti-thermal decomposition agents, and lubricants, especially for the preparation of molded bodies / articles. These further added substances can be mixed at any stage of the preparation process, but are preferably mixed at an early stage in order to benefit earlier from the stabilizing effect (or other specific effects) of the added substances. For other commonly used auxiliaries and additives, see, for example, "Plastics Additives Handbook", ed. and Müller, 4th edition, Hanser Verlag, Munich, 1996.

[0101] Examples of suitable pigments include titanium dioxide, phthalocyanine, ultramarine blue, iron oxide or carbon black, and also the entire class of organic pigments.

[0102] Examples of suitable colorants include all dyes which can be used for transparent, semi-transparent or opaque coloring of polymers, in particular those which are suitable for coloring styrene copolymers.

[0103] Examples of suitable flame retardants that may be used include halogen- or phosphorus-containing compounds known to those skilled in the art, magnesium hydroxide, and other commonly used compounds or mixtures thereof.

[0104] Examples of suitable antioxidants include sterically hindered monocyclic or polycyclic phenolic antioxidants, which may contain various substitutions and may also be bridged by substituents. These include not only monomeric compounds, but also oligomeric compounds which may be composed of multiple phenolic units. Hydroquinone and hydroquinone analogs are also suitable, as are substituted compounds, and antioxidants based on tocopherol and its derivatives are also suitable. Mixtures of different antioxidants can also be used. In principle, any compound commonly used in the industry or suitable for styrene copolymers can be used, such as the antioxidants of the Irganox series. In addition to the phenolic antioxidants mentioned by way of example above, so-called co-stabilizers can also be used, in particular phosphorus- or sulfur-containing co-stabilizers. These phosphorus- or sulfur-containing co-stabilizers are known to those skilled in the art.

[0105] Examples of suitable light stabilizers include various substituted resorcinols, salicylates, benzotriazoles, and benzophenones.

[0106] Suitable matting agents include not only talc, glass microspheres or metal carbonates (e.g. MgCO 3 、CaCO 3 ) and other inorganic substances, including polymer particles, especially those with a diameter D 50 Spherical particles larger than 1 μm. Based on, for example, methyl methacrylate, styrene compounds, acrylonitrile or mixtures thereof. In addition, polymers containing copolymerized acidic and / or basic monomers can also be used.

[0107] Examples of suitable anti-drip agents include polytetrafluoroethylene (Teflon) polymers and ultra-high molecular weight polystyrene (weight average molar mass Mw above 2,000,000).

[0108] Examples of fiber / powder fillers include carbon or glass fibers in the form of glass fiber fabrics, glass mats or filament glass rovings, chopped glass, glass beads, and wollastonite, with glass fibers being particularly preferred. When glass fibers are used, they may be treated with sizing agents and coupling agents to improve compatibility with the blending components. The incorporated glass fibers may be in the form of short glass fibers or in the form of continuous filaments (rovings).

[0109] Examples of suitable particulate fillers include carbon black, amorphous silica, magnesium carbonate, quartz powder, mica, bentonite, talc, feldspar or especially calcium silicates such as wollastonite and kaolin.

[0110] Examples of suitable antistatic agents include amine derivatives such as N,N-bis(hydroxyalkyl)alkylamines or N,N-bis(hydroxyalkyl)alkyleneamines, polyethylene glycol esters, copolymers of ethylene oxide glycol and propylene oxide glycol (especially diblock or triblock copolymers of ethylene oxide blocks and propylene oxide blocks), glyceryl monostearate and glyceryl distearate, and mixtures thereof.

[0111] Examples of suitable stabilizers include hindered phenols, also vitamin E / compounds with similar structures, and butylated condensation products of p-cresol and dicyclopentadiene. HALS stabilizers (hindered amine light stabilizers), benzophenone, resorcinol, salicylates, benzotriazoles are also suitable. Other suitable compounds include, for example, thiocarboxylates. Thiopropionic acid C 6 -C 20 Alkyl esters, especially stearyl and lauric esters. It is also possible to use dilauryl thiodipropionic acid (dilauryl thiodipropionate), distearyl thiodipropionic acid (distearyl thiodipropionate) or mixtures thereof.

[0112] Examples of other additives include HALS absorbers, such as bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, or UV absorbers, such as 2H-benzotriazol-2-yl-(4-methylphenol). Such additives are typically used in an amount of 0.01-2% by weight based on the total virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS).

[0113] Suitable lubricants and release agents include stearic acid, stearyl alcohol, stearic acid esters, amide waxes (bisstearamide), polyolefin waxes and / or generally higher fatty acids and their derivatives and corresponding fatty acid mixtures. Particularly suitable is ethylene-bisstearamide. Based on the total native acrylonitrile-butadiene-styrene copolymer composition (v-ABS), the amount of these additives is preferably 0.05-5% by weight. Preferred lubricants can be selected from long-chain fatty acids, such as stearic acid or behenic acid, fatty acid salts (such as calcium stearate or zinc stearate), fatty acid esters (such as stearyl stearate or pentaerythritol stearate), amide derivatives of fatty acids (such as ethylenebisstearylamide, erucamide, ), phosphates (such as tricalcium phosphate), hydrocarbon waxes such as microcrystalline wax and paraffin wax (such as ), and fumed silica (such as Generally, fatty acids are linear or branched, saturated or unsaturated C 5 -C 25 Alkyl chain carboxylic acid.

[0114] Suitable additives are also silicone oils, oligomeric isobutylene or similar substances. When used, the amount is usually 0.001 to 3% by weight, based on the total virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS).

[0115] An example of a processing aid is a homogeneously miscible oil or oil mixture, especially selected from mineral oil (medical grade mineral oil), natural vegetable oil (also known as vegetable oil) and silicone oil, which can be used in an amount of 0.1-5% by weight, preferably 0.5-3% by weight, based on the total virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS).

[0116] Processing aids and stabilizers, such as UV stabilizers, heat stabilizers (e.g., the butylated reaction product of p-cresol and dicyclopentadiene, Wingstay L from Omnova, or dilauryl thiodipropionic acid, Irganox PS800 from BASF), lubricants and antistatic agents (e.g., ethylene oxide-propylene oxide copolymers, such as Pluronic from BASF), when used, are typically used in amounts of 0.01 to 5 weight percent, based on the total virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS).

[0117] The individual added substances are usually used in the respective customary amounts.

[0118] Recycled acrylonitrile-butadiene-styrene copolymer (r-ABS)

[0119] Preferably, the recycled acrylonitrile-butadiene-styrene copolymer (r-ABS) is a recycled material obtained from the recycling of durable goods, especially post-consumer durable goods, which are preferably selected from automotive equipment, household appliances and electrical equipment.

[0120] Generally, durable goods are understood to be goods such as household appliances, machinery, sports equipment, consumer electronics, and automobiles that are not rapidly consumed or destroyed in use but are expected to continue in use and produce utility for a long period of time, especially three years or more.

[0121] Preferably, the recycled acrylonitrile-butadiene-styrene copolymer (r-ABS) comprises at least 90% by weight of acrylonitrile-butadiene-styrene copolymer-type polymer based on r-ABS. The recycled acrylonitrile-butadiene-styrene copolymer (r-ABS) can be, for example, a mixture of different grades of acrylonitrile-butadiene-styrene copolymer, or the r-ABS component can consist of one grade of r-ABS. For example, the r-ABS component can be obtained from waste and defective parts in the manufacturing process of ABS molded products.

[0122] In a preferred embodiment, the at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) is a recycled material comprising (or consisting of):

[0123] E: at least one acrylonitrile-butadiene-styrene copolymer E;

[0124] F: at least one styrene-acrylonitrile copolymer F; and

[0125] G: Optionally, at least one additive G.

[0126] Typically, the at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) is a recycled material comprising (or consisting of):

[0127] E: 20-60% by weight of at least one graft copolymer E, comprising:

[0128] E1: 40-85% by weight of graft base A1, based on the solid content of graft copolymer E, comprising:

[0129] E11: 0-21% by weight, based on the graft base E1, of at least one vinyl aromatic monomer, in particular styrene, and

[0130] E12: 79-100% by weight butadiene, based on graft base E1,

[0131] wherein the sum of E11 and E12 is 100% by weight of the grafting matrix E1; and

[0132] E2: 15-60% by weight, based on the solid content of the graft copolymer E, of at least one graft shell E2, comprising:

[0133] E21: 70-90% by weight of styrene and / or α-methylstyrene, especially styrene, based on the graft shell E2, and

[0134] E22: 10-30% by weight of acrylonitrile and optionally methyl methacrylate, especially acrylonitrile, based on the graft shell E2;

[0135] wherein the sum of E21 and E22 is 100% by weight of the graft shell E2; and

[0136] Wherein, the sum of the graft matrix E1 and the graft shell E2 is 100% by weight of the graft copolymer E;

[0137] F: 40-80% by weight of at least one thermoplastic copolymer F, obtainable from:

[0138] F1: 20-31% by weight of acrylonitrile, based on copolymer F, and

[0139] F2: 69-80% by weight of styrene or α-methylstyrene or a mixture of styrene and α-methylstyrene, based on copolymer F;

[0140] wherein the sum of F1 and F2 is 100% by weight of the thermoplastic copolymer F; and

[0141] G: 0-5% by weight of at least one other additive G;

[0142] The sum of E, F and G is 100% by weight of the recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS).

[0143] For the preferred embodiments of components E, F, E1, E2, E11, E12, E21, E22, F1 and F2, the definitions of components A, B, A1, A2, A11, A12, A21, A22, B1 and B2 apply, respectively. However, from the perspective of chemical composition, the recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) and the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) may be the same as or different from each other.

[0144] The other additives G are generally known additives for styrene polymers and copolymers and compositions thereof. Substances that may be present as additives or auxiliaries are polymer additives known to those skilled in the art, such as the additives C described above.

[0145] Acrylonitrile-butadiene-styrene copolymer composition (ABS)

[0146] As mentioned above, the present invention relates to a method for improving the gloss stability of an acrylonitrile-butadiene-styrene copolymer composition (ABS) by mixing a virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) with 10-99% by weight of at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) based on the acrylonitrile-butadiene-styrene copolymer composition (ABS), wherein the at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) has been through at least one separate thermal compounding step prior to the mixing step.

[0147] According to one aspect of the present invention, the present invention also relates to an acrylonitrile-butadiene-styrene copolymer composition (ABS) with improved gloss stability, comprising:

[0148] v-ABS: 1-90% by weight, preferably 11-70% by weight, more preferably 20-60% by weight, usually 25-55% by weight or 30-50% by weight of at least one virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) based on acrylonitrile-butadiene-styrene copolymer composition (ABS);

[0149] r-ABS: 10-99% by weight, preferably 30-89% by weight, more preferably 40-80% by weight, usually 45-75% by weight or 50-70% by weight of at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) based on an acrylonitrile-butadiene-styrene copolymer composition (ABS);

[0150] K: 0-10% by weight of at least one additive K;

[0151] P: 0-15% by weight, preferably 0-10% by weight, more preferably 0-5% by weight of at least one other polymer P different from the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) and the recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS), based on the acrylonitrile-butadiene-styrene copolymer composition (ABS);

[0152] wherein the sum of (v-ABS), (r-ABS), K and P is 100% by weight of a virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS), and

[0153] Wherein, the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) is a virgin material, comprising:

[0154] A: 20-60% by weight of at least one graft copolymer A, comprising:

[0155] A1: Based on the solid content of the graft copolymer A, 40-85% by weight of the graft matrix A1, comprising:

[0156] A11: 0-21% by weight, based on the graft base A1, of at least one vinyl aromatic monomer, in particular styrene, and

[0157] A12: 79-100% by weight of butadiene, based on the grafting matrix A1;

[0158] wherein the sum of A11 and A12 is 100% by weight of the grafting matrix A1; and

[0159] A2: 15-60% by weight, based on the solid content of the graft copolymer A, of at least one graft shell A2, comprising:

[0160] A21: 70 to 90% by weight, based on the graft shell A2, of styrene and / or α-methylstyrene, in particular styrene, and

[0161] A22: 10-30% by weight of acrylonitrile and optionally methyl acrylate, in particular acrylonitrile, based on the graft shell A2,

[0162] wherein the sum of A21 and A22 is 100% by weight of the graft shell A2; and

[0163] wherein the sum of the graft matrix A1 and the graft shell A2 is 100% by weight of the graft copolymer A;

[0164] B: 40-80% by weight of at least one thermoplastic copolymer B, comprising:

[0165] B1: 20-31% by weight of acrylonitrile, based on copolymer B, and

[0166] B2: 69-80% by weight of styrene or α-methylstyrene or a mixture of styrene and α-methylstyrene, based on copolymer B;

[0167] Wherein, the sum of B1 and B2 is 100% by weight of thermoplastic copolymer B;

[0168] C: 1-5% by weight of at least one additive C,

[0169] Wherein, the sum of A, B and C is equal to 100 weight percent of the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS).

[0170] Components v-ABS, r-ABS, A, B, A1, A2, A11, A12, A21, A22, B1 and B2 and preferred embodiments thereof are as described above.

[0171] The acrylonitrile-butadiene-styrene copolymer composition (ABS) of the present invention may contain a well-known additive C as a component of the original acrylonitrile-butadiene-styrene copolymer v-ABS. Suitable additives C are as described above. In addition, the acrylonitrile-butadiene-styrene copolymer composition (ABS) of the present invention may contain a well-known additive G derived from a recycled acrylonitrile-butadiene-styrene copolymer (r-ABS), but not including the amount described as additive C. Additive G can be selected from the additives C described above. Additive G may be the same as or different from additive C.

[0172] In addition, if deemed necessary, the acrylonitrile-butadiene-styrene copolymer composition (ABS) may contain up to 10% by weight, preferably up to 5% by weight, based on the total acrylonitrile-butadiene-styrene copolymer composition (ABS), of one or more other additives K, which do not originate from v-ABS or r-ABS. Preferably, the acrylonitrile-butadiene-styrene copolymer composition (ABS) may contain one or more additives C, G and K in a total amount of 0.01-10% by weight, preferably 0.1-5%, more preferably 0.1-2.5% by weight, based on the total acrylonitrile-butadiene-styrene copolymer composition (ABS). The other additive K is generally selected from the known additives for styrene polymers and copolymers and compositions thereof. Substances that can be used as additives K are polymer additives known to those skilled in the art, as described above as additives C. The individual added substances are generally used in their respective conventional amounts.

[0173] Based on the total acrylonitrile-butadiene-styrene copolymer composition (ABS), the acrylonitrile-butadiene-styrene copolymer composition (ABS) may further contain up to 15% by weight, preferably up to 10% by weight, more preferably up to 5% by weight of one or more other polymers P different from v-ABS and r-ABS. The polymer P is usually derived from recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS), because it is usually difficult to obtain recycled polymer materials with a purity of 100% by weight or close to 100% by weight.

[0174] Preferably, the acrylonitrile-butadiene-styrene copolymer composition (ABS) may contain 0.01-15 wt %, preferably 0.1-10 wt %, preferably 0.1-5 wt % of one or more polymers P, based on the total acrylonitrile-butadiene-styrene copolymer composition (ABS).

[0175] Preferably, the acrylonitrile-butadiene-styrene copolymer composition (ABS) comprises less than 5 wt. %, preferably less than 2 wt. %, more preferably less than 1 wt. % of one or more polymers P, based on the total acrylonitrile-butadiene-styrene copolymer composition (ABS).

[0176] Typical examples of polymers P include polyolefins, polycarbonates, polyester carbonates, polyesters, polyamides, polyoxyalkylenes, polyarylether sulfides, polyetherketones, polyvinyl chlorides and mixtures thereof.

[0177] Preparation method of acrylonitrile-butadiene-styrene copolymer composition (ABS)

[0178] Further, the present invention relates to a method for preparing the acrylonitrile-butadiene-styrene copolymer composition (ABS) of the present invention. The present invention particularly relates to a method for preparing the acrylonitrile-butadiene-styrene copolymer composition (ABS) as described above, wherein the components v-ABS, r-ABS and optionally K and / or P are melt compounded at a temperature range of 180-280°C, preferably 200-250°C.

[0179] The acrylonitrile-butadiene-styrene copolymer composition (ABS) can be prepared by methods known per se. For example, an extruder (such as a co-rotating or counter-rotating single screw or twin screw extruder), or other conventional kneading equipment (such as a continuous or intermittent kneader), a Brabender mixer or a Banbury mixer can be used to prepare the acrylonitrile-butadiene-styrene copolymer composition (ABS).

[0180] The kneading elements should ensure sufficient homogeneity of the components to ensure micromixing. The acrylonitrile-butadiene-styrene copolymer composition (ABS) of the present invention can be obtained by mixing and homogenizing the above-mentioned components v-ABS, r-ABS and optionally K and / or P by conventional methods of plastics technology, wherein the order of adding the components can be changed.

[0181] Preferably, the recycled ABS component (r-ABS) may be pre-treated, for example by homogenization, grinding, pulverization and / or micronization, prior to melt compounding with the virgin ABS component (v-ABS).

[0182] Use of acrylonitrile-butadiene-styrene copolymer composition (ABS)

[0183] Further, the present invention relates to the use of the acrylonitrile-butadiene-styrene copolymer composition (ABS) of the present invention as described above, for preparing molded articles (shaped articles) for various applications, such as applications in the automotive field, electronics, daily necessities, construction, health care products, packaging, sports and leisure products. The acrylonitrile-butadiene-styrene copolymer composition (ABS) of the present invention can be used to produce any type of molded articles. These products can be produced by injection molding, extrusion and blow molding processes. Another processing is to make molded articles from previously produced sheets or films by thermoforming and film overmolding processes. The acrylonitrile-butadiene-styrene copolymer composition (ABS) of the present invention is particularly used for injection molding processes. Examples of these molded articles include films, profiles, housing parts of any type, such as for household appliances such as juicers, coffee machines, blenders, office equipment such as displays, printers, copiers, exterior and interior parts of automobiles, sheets, pipes, electrical installation pipes, windows, doors and other profiles in the field of construction (decoration for indoor and outdoor applications), and parts for electrical and electronic devices such as switches, plugs and sockets.

[0184] Moulded articles made of acrylonitrile-butadiene-styrene copolymer (ABS)

[0185] Further, the present invention relates to a molded article made of the acrylonitrile-butadiene-styrene copolymer composition (ABS) of the present invention as described above. The molded article can be selected from any type of molded article, for example, as described above. Specifically, the molded article can be, for example, interior accessories for rail vehicles, ships, aircraft, buses and other motor vehicles, body parts for motor vehicles, housings for electrical equipment including small transformers, housings for equipment for processing and transmitting information, housings and protective layers for medical equipment, massage equipment and housings thereof, children's toy vehicles, sheet wall components, housings for safety equipment, insulated transport containers, appliances for raising or caring for small animals, molded articles for sanitary equipment, protective grilles for ventilator openings, molded articles for garden sheds and tool sheds, housings for gardening equipment.

[0186] The invention will be further illustrated by the following examples and patent claims. DETAILED DESCRIPTION

[0187] Example

[0188] The r-ABS and v-ABS components were co-extruded to prepare an ABS copolymer composition as shown in Table 1.

[0189] v-ABS is a polymer blend containing about 67% by weight of a SAN-matrix (Mw about 135,000 g / mol) and about 27-32% by weight of an ABS copolymer with a bimodal rubber particle size distribution. Both components are produced by INEOS Styrolution's polymerization process. The v-ABS product also contains additives such as stabilizers, waxes and lubricants.

[0190] r-ABS is a copolymer blend obtained by recycling post-consumer products. Table 1 Sample ABS composition sample r-ABS v-ABS Comparative Example 1 0 100 Example 1 50 50 Example 2 70 30 Comparative Example 2 100 0

[0191] Several ABS plaques were injection molded at a mass temperature of T = 250°C to obtain high gloss step polymer plaques (120 mm x 60 mm).

[0192] The samples were artificially aged by heat treatment in an oven at 80°C. To evaluate the optical changes, the injection molded step plates were kept in the oven for 1000 hours and the optical properties of the samples were measured according to the following conditions:

[0193] Colorimetric measurement:

[0194] Colorimeter: X-Rite Ci7860 benchtop spectrophotometer

[0195] Measurement geometry: d:8°, Specular Constrained Reflectivity Measurement (SCI)

[0196] Aperture: Illuminant: D65; Observer angle: 10°

[0197] Chromaticity value output: CIE L*a*b*

[0198] Gloss measurement:

[0199] Colorimeter: BYK Instruments spectro-guide 45 / 0gloss

[0200] Measurement geometry: 45°c:0°, reflection measurement + 60° gloss measurement

[0201] Aperture: 11mm; Light source: D65; Observer angle: 10°, Gloss output: GU

[0202] The measurement results are summarized in Table 2. Table 2 Optical properties after artificial aging.

[0203] The visual effect was determined by visual inspection of the panels with the naked eye. It was observed that the compositions of Examples 1 and 2 according to the invention and the composition of Comparative Example 1 had no color variation over the visible surface of the panel. In contrast, the composition of Comparative Example 2 exhibited color fluctuations. Such color fluctuations make these compositions unsuitable for many applications.

[0204] From the data shown in Table 2, it can be seen that the use of a blend of virgin ABS and recycled ABS can improve the gloss stability of the high gloss sample surface, especially after being heated in an 80°C furnace for 1000 hours (i.e., the gloss difference is reduced).

[0205] This suggests that using recycled ABS material helps reduce the variation of ABS surface optical effects in practice, especially under continuous thermal stress, compared to pure ABS compositions. This result is also seen after more than 42 days of heat treatment.

[0206] The molded articles made from this composition have excellent properties and can be produced at low cost. It also has ecological advantages.

Claims

1. A method for improving the gloss stability of an acrylonitrile-butadiene-styrene copolymer composition (ABS), the method comprising mixing a virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) with 10-99% by weight of at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) based on the acrylonitrile-butadiene-styrene copolymer composition (ABS), wherein: The at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) is subjected to at least one separate thermal compounding step prior to the mixing step, wherein the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) is a virgin material comprising: A: 20-60% by weight of at least one graft copolymer A, comprising: A1: Based on the solid content of the graft copolymer A, 40-85% by weight of the graft matrix A1, comprising: A11: 0-21% by weight, based on the graft base A1, of at least one vinyl aromatic monomer, especially styrene, and A12: 79-100% by weight of butadiene, based on the grafting matrix A1, wherein the sum of A11 and A12 is 100% by weight of the grafting matrix A1; and A2: 15-60% by weight, based on the solid content of the graft copolymer A, of at least one graft shell A2, comprising: A21: 70-90% by weight of styrene and / or α-methylstyrene, especially styrene, based on the graft shell A2, and A22: 10-30% by weight of acrylonitrile based on the graft shell A2, wherein the sum of A21 and A22 is 100% by weight of the graft shell A2; and Wherein, the sum of the graft matrix A1 and the graft shell A2 is 100% by weight of the graft copolymer A; B: 40-80% by weight of at least one thermoplastic copolymer B obtained from: B1: 20-31% by weight of acrylonitrile based on the copolymer B, and B2: based on the copolymer B, 69-80% by weight of styrene or α-methylstyrene or a mixture of styrene and α-methylstyrene; wherein the sum of B1 and B2 is 100% by weight of the thermoplastic copolymer B; and C: 0-5% by weight of at least one additive C; Wherein, the sum of A, B and C is equal to 100 weight percent of the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS).

2. The method for improving the surface gloss stability of an acrylonitrile-butadiene-styrene copolymer composition (ABS) according to claim 1, characterized in that: The method includes mixing the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) with 30-89 weight percent of a recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) based on the acrylonitrile-butadiene-styrene copolymer composition (ABS).

3. The method for improving the surface gloss stability of an acrylonitrile-butadiene-styrene copolymer composition (ABS) according to claim 1 or 2, characterized in that: The method includes mixing the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) with 40-80 weight percent of a recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) based on the acrylonitrile-butadiene-styrene copolymer composition (ABS).

4. The method for improving the surface gloss stability of an acrylonitrile-butadiene-styrene copolymer composition (ABS) according to any one of claims 1 to 3, characterized in that: The virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) comprises at least one 50 Graft copolymer A with a particle size distribution in the range of 70 nm to 550 nm.

5. The method for improving the surface gloss stability of an acrylonitrile-butadiene-styrene copolymer composition (ABS) according to any one of claims 1 to 4, characterized in that: The at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) is a recycled material comprising: E: at least one acrylonitrile-butadiene-styrene copolymer E; F: at least one styrene-acrylonitrile copolymer F; and G: Optionally, at least one additive G.

6. The method for improving the surface gloss stability of an acrylonitrile-butadiene-styrene copolymer composition (ABS) according to any one of claims 1 to 5, characterized in that: The at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) is a recycled material comprising: E: 20-60% by weight of at least one graft copolymer E, comprising: E1: Based on the solid content of the graft copolymer E, 40-85% by weight of a graft matrix A1, comprising: E11: 0-21% by weight, based on the graft base E1, of at least one vinyl aromatic monomer, especially styrene, and E12: 79-100% by weight of butadiene, based on the grafting matrix E1, wherein the sum of E11 and E12 is 100% by weight of the grafting matrix E1; and E2: 15-60% by weight, based on the solid content of the graft copolymer E, of at least one graft shell E2, comprising: E21: 70-90% by weight of styrene and / or α-methylstyrene, especially styrene, based on the graft shell E2, and E22: 10-30% by weight of acrylonitrile and optionally methyl methacrylate, especially acrylonitrile, based on the graft shell E2; wherein the sum of E21 and E22 is 100% by weight of the graft shell E2; and Wherein, the sum of the graft matrix E1 and the graft shell E2 is 100% by weight of the graft copolymer E; F: 40-80% by weight of at least one thermoplastic copolymer F, obtainable from: F1: 20-31% by weight of acrylonitrile, based on the copolymer F, and F2: based on the copolymer F, 69-80% by weight of styrene or α-methylstyrene or a mixture of styrene and α-methylstyrene; wherein the sum of F1 and F2 is 100% by weight of the thermoplastic copolymer F; and G: 0-5% by weight of at least one other additive G; The sum of E, F and G is 100% by weight of the recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS).

7. The method for improving the surface gloss stability of an acrylonitrile-butadiene-styrene copolymer composition (ABS) according to any one of claims 1 to 6, characterized in that: Gloss stability is determined by comparing the surface gloss of molded articles formed from acrylonitrile-butadiene-styrene copolymer compositions (ABS) before and after aging at 80°C for 1000 hours with the surface gloss of molded articles formed from virgin acrylonitrile-butadiene-styrene copolymer compositions (v-ABS).

8. An acrylonitrile-butadiene-styrene copolymer composition (ABS) having improved gloss stability, comprising: v-ABS: 1-90% by weight, preferably 11-70% by weight, more preferably 20-60% by weight, usually 25-55% by weight or 30-50% by weight of at least one virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS), based on the acrylonitrile-butadiene-styrene copolymer composition (ABS); r-ABS: 10-99% by weight, preferably 30-89% by weight, more preferably 40-80% by weight, usually 45-75% by weight or 50-70% by weight of at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS), based on the acrylonitrile-butadiene-styrene copolymer composition (ABS); K: 0-8% by weight of at least one additive K; P: based on the acrylonitrile-butadiene-styrene copolymer composition (ABS), 0-15% by weight, preferably 0-10% by weight, more preferably 0-5% by weight of at least one other polymer P different from the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) and the recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS); in, The sum of (v-ABS), (r-ABS), K and P is 100% by weight of the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS), and Wherein, the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) is a virgin material, comprising: A: 20-60% by weight of at least one graft copolymer A, comprising: A1: Based on the solid content of the graft copolymer A, 40-85% by weight of the graft matrix A1, comprising: A11: 0-21% by weight, based on the graft base A1, of at least one vinyl aromatic monomer, especially styrene, and A12: 79-100% by weight of butadiene based on the grafting matrix A1; wherein the sum of A11 and A12 is 100% by weight of the grafting matrix A1; and A2: 15-60% by weight, based on the solid content of the graft copolymer A, of at least one graft shell A2, comprising: A21: 70-90% by weight of styrene and / or α-methylstyrene, especially styrene, based on the graft shell A2, and A22: 10-30% by weight of acrylonitrile and optionally methyl acrylate, in particular acrylonitrile, based on the graft shell A2, wherein the sum of A21 and A22 is 100% by weight of the graft shell A2; and Wherein, the sum of the graft matrix A1 and the graft shell A2 is 100% by weight of the graft copolymer A; B: 40-80% by weight of at least one thermoplastic copolymer B, comprising: B1: 20-31% by weight of acrylonitrile based on the copolymer B, and B2: based on the copolymer B, 69-80% by weight of styrene or α-methylstyrene or a mixture of styrene and α-methylstyrene; Wherein, the sum of B1 and B2 is 100% by weight of the thermoplastic copolymer B; C: 1-5% by weight of at least one additive C, Wherein, the sum of A, B and C is equal to 100 weight percent of the virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS).

9. The acrylonitrile-butadiene-styrene copolymer composition (ABS) according to claim 8, characterized in that: The at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) is a recycled material obtained from recycling durable goods, especially post-consumer durable goods.

10. The acrylonitrile-butadiene-styrene copolymer composition (ABS) according to claim 8 or 9, characterized in that: The virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS) comprises at least one 50 Graft copolymer A with a particle size distribution in the range of 70 nm to 550 nm.

11. The acrylonitrile-butadiene-styrene copolymer composition (ABS) according to any one of claims 8 to 10, characterized in that: The at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) is a recycled material comprising: E: 20-60% by weight of at least one graft copolymer E, comprising: E1: Based on the solid content of the graft copolymer E, 40-85% by weight of a graft matrix A1, comprising: E11: 0-21% by weight, based on the graft base E1, of at least one vinyl aromatic monomer, especially styrene, and E12: 79-100% by weight of butadiene, based on the grafting matrix E1, wherein the sum of E11 and E12 is 100% by weight of the grafting matrix E1; and E2: 15-60% by weight, based on the solid content of the graft copolymer E, of at least one graft shell E2, comprising: E21: 70-90% by weight of styrene and / or α-methylstyrene, especially styrene, based on the graft shell E2, and E22: 10-30% by weight of acrylonitrile and optionally methyl methacrylate, especially acrylonitrile, based on the graft shell E2; wherein the sum of E21 and E22 is 100% by weight of the graft shell E2; and Wherein, the sum of the graft matrix E1 and the graft shell E2 is 100% by weight of the graft copolymer E; F: 40-80% by weight of at least one thermoplastic copolymer F obtained from: F1: 20-31% by weight of acrylonitrile, based on the copolymer F, and F2: based on the copolymer F, 69-80% by weight of styrene or α-methylstyrene or a mixture of styrene and α-methylstyrene; wherein the sum of F1 and F2 is 100% by weight of the thermoplastic copolymer F; and G: 0-5% by weight of at least one other additive G; The sum of E, F and G is 100% by weight of the recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS).

12. A method for preparing an acrylonitrile-butadiene-styrene copolymer composition (ABS) according to any one of claims 8 to 11, characterized in that: The at least one virgin acrylonitrile-butadiene-styrene copolymer composition (v-ABS), at least one recycled acrylonitrile-butadiene-styrene copolymer composition (r-ABS) and optionally at least one additive K and / or at least one other polymer P are melt mixed in a temperature range of 180-280°C.

13. A molded article made of the acrylonitrile-butadiene-styrene copolymer composition (ABS) according to any one of claims 8 to 11.

14. Use of an acrylonitrile-butadiene-styrene copolymer composition (ABS) obtained according to the process of any one of claims 1 to 7 as a molding material in an extrusion process.

15. Use of the acrylonitrile-butadiene-styrene copolymer composition (ABS) according to any one of claims 8 to 11 as a molding material in an extrusion process.